Beliefs and attributions: Insider accounts of men's place in early childhood education and care. (June 2020) - Sullivan, Victoria; Coles, Laetitia; Xu, Yuwei; Perales, Francisco; Thorpe, Karen
Theoretical perspectives, and a large body of empirical research examining sex-segregated occupations, identify the attitudinal barriers of the majority as pivotal for both workplace well-being and the retention of minorities. Globally, where more than 90% of the early childhood education and care workforce is female, understanding the attitudes of the majority is critical in informing actions to sustain men's participation. So too are female educators' understanding, acceptance and responses to the attitudes of other key stakeholders. The extent to which decisions in the workplace reflect personal, organisational or parent perspectives is not well understood. In this study, the authors analyse interview data from the female majority to distinguish personal voice and attributed beliefs regarding the inclusion of men in the early childhood education and care workplace. They analyse interview data from 96 women working as educators in a representative sample of long-day-care and kindergarten services in Queensland, Australia. The analyses suggest that the view of male educators as assets was claimed, while concerns about risk or competency were typically attributed to others. Attributed views were not often contested, but instead accepted or excused. The findings suggest that while the inclusion of men in the early childhood education and care workforce is explicitly accepted by female colleagues, actions within the workforce may be influenced by the attitudes of those outside or by latent personal attitudes distanced by positioning as the voice of others.